How managers describe themselves in a job context - D. J.W. Strümpfer (South African Journal of Business Management, 1983)
By means of self-report inventories, 163 White, male, English-speaking managers described their subjective experiences of job demands and their views of themselves as working people. The mean scores on the Jenkins Activity Survey (measuring Type A - B behaviour) were well above the means of high-scoring American samples. A factor analysis of all scores revealed four interpretable factors. 'Hard Managerial Work' reflected a heavy work load, long hours worked, high utilization of abilities, high participation, and Type A behaviour, with emphasis on hard-driving competitiveness, and role clarity - but all of these experienced rather positively. Another positive factor, 'Individualistic Dedication', reflected high job involvement, full utilization of abilities and low role conflict - more as a matter of personal participation than of reaction to demands. 'Subjective Distress' reflected exhaustion, role conflict, absence of friendliness, joylessness and Type A behaviour, with an emphasis on the rushed aspect of speed and impatience. The second negative factor, 'Vulnerability', reflected high levels of social support from superiors and co-workers, need for role clarity, joylessness, and low personality hardiness.
Keywords: 650